Manajemen perkotaan. Aktor, organisasi dan pengelolaan daerah perkotaan di Indonesia - NURMANDI, Achmad (Lingkaran, 1999)
Manajemen perkotaan. Aktor, organisasi dan pengelolaan daerah perkotaan di Indonesia